2016
DOI: 10.1111/auar.12110
|View full text |Cite
|
Sign up to set email alerts
|

Do ATMs Increase Technical Efficiency of Banks in a Developing Country? Evidence from Indian Banks

Abstract: Prior studies have confirmed that the greater the investment in information technology (IT),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
(93 reference statements)
1
20
0
2
Order By: Relevance
“…Despite the advantages of innovation in the banking sector, some empirical studies mostly from developing nations indicated that innovation technology negatively affects overall bank performance [43,44]. Le and Ngo [40] asserted that, regardless of the absence of an adequate wide variety of clients, higher costs in the infrastructure of Internet banking impact the benefit of banks negatively.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
“…Despite the advantages of innovation in the banking sector, some empirical studies mostly from developing nations indicated that innovation technology negatively affects overall bank performance [43,44]. Le and Ngo [40] asserted that, regardless of the absence of an adequate wide variety of clients, higher costs in the infrastructure of Internet banking impact the benefit of banks negatively.…”
Section: Eoretical Review Of the Literature And The Conceptualmentioning
confidence: 99%
“…Raina and Sharma (2013) concluded that the substantial inefficiency that was present among the PSBs over the period 2006–2011 was not because of underutilization of financial resources by the managers but due to the regulatory environment. Sathye and Sathye (2017) have performed an intriguing investigation on whether ATMs increment technical efficiency of the Indian banks. Contrasting to other similar studies on banks of developed countries, they proposed, based on their finding that there is an adverse effect of ATM intensity on the bootstrap DEA technical efficiency, that anticipated results would not be produced without automation of the processes related to ATMs.…”
Section: Literature On Efficiency In Bankingmentioning
confidence: 99%
“…Previous studies have examined the appropriate inputs for DEA applications in the banking industry. Some of the outputs that are currently widely used are total loans (Chen & Yeh 1998;Diallo 2918;Howland & Rowse 2006;Sufian & Noor 2009;Wu et al 2006;Golany & Storbeck 1999;Resti 1997;Felix et al 1998), interest income and non-interest income (Felix et al 1998;Sakar 2006;Mukherjee et al 2002;Sathye & Sathye 2017). Total loans and interest income are very appropriate measures of output to use in determining the technical efficiency of RDBs as their income is dominated by loan disbursement, which carries an income generation capacity.…”
Section: Literature Review Bank Efficiency and Data Envelopment Analysismentioning
confidence: 99%